Adiabaticity Engineered Silicon Polarization Independent 3-dB Coupler for the O-Band - Hung-Ching Chung; Chih-Hsien Chen; Guan-Xun Lu; Yung-Jr Hung; Shuo-Yen Tseng (IEEE Photonics Journal, 2023)
We demonstrate a compact and broadband polarization independent 3-dB coupler for the O-band on silicon-on-insulator platform. Using the multi-parameter adiabaticity engineering protocol, unwanted coupling between eigenmodes in mode evolution couplers are redistributed for dual polarization modes and multiple wavelengths, resulting in a large operating bandwidth for both TE and TM polarizations. The fabricated device has a bandwidth of 70 nm with a compact mode evolution region of 27 μm.